Math, asked by rh8853815, 4 months ago

nsjwjwjsnsbsbsbsbsbbsn​

Attachments:

Answers

Answered by xInvincible
0

\huge\fcolorbox{red}{cyan}{x = 2}

Explaination :-

\frac{2}{3}(x-3) = 1 - \frac{5}{6}(3x-4)  \\ => \frac{2x}{3}-\frac{6}{3} = 1 - \frac{15x}{6} + \frac{20}{6}  \\ => \bf{Lets\:Convert\:Them\:In\:Simplest\:Form}  \\ => \frac{2x}{3} - 2 = 1 - \frac{5x}{2}+\frac{10}{3}  \\ => \frac{2x-6}{3} = \frac{6-15x+20}{6} \\ => \frac{2x-6}{3} = \frac{26-15x}{6}  \\ => 6(2x-6) = 3(26 - 15x)  \\ => 12x - 36 = 78 - 45x  \\ => 12x + 45 x = 78 + 36  \\ => 57x = 114  \\ =>x = \frac{114}{57}  \\ => \boxed{x = 2}

If it helped then Please follow

Answered by mehak238517
0

Answer:

Explaination :-

\begin{gathered}\frac{2}{3}(x-3) = 1 - \frac{5}{6}(3x-4) \\ = > \frac{2x}{3}-\frac{6}{3} = 1 - \frac{15x}{6} + \frac{20}{6} \\ = > \bf{Lets\:Convert\:Them\:In\:Simplest\:Form} \\ = > \frac{2x}{3} - 2 = 1 - \frac{5x}{2}+\frac{10}{3} \\ = > \frac{2x-6}{3} = \frac{6-15x+20}{6} \\ = > \frac{2x-6}{3} = \frac{26-15x}{6} \\ = > 6(2x-6) = 3(26 - 15x) \\ = > 12x - 36 = 78 - 45x \\ = > 12x + 45 x = 78 + 36 \\ = > 57x = 114 \\ = > x = \frac{114}{57} \\ = > \boxed{x = 2}\end{gathered}32(x−3)=1−65(3x−4)=>32x−36=1−615x+620=>LetsConvertThemInSimplestForm=>32x−2=1−25x+310=>32x−6=66−15x+20=>32x−6=626−15x=>6(2x−6)=3(26−15x)=>12x−36=78−45x=>12x+45x=78+36=>57x=114=>x=57114=>x=2

If 

Similar questions